2017
DOI: 10.1002/bit.26322
|View full text |Cite
|
Sign up to set email alerts
|

The amino‐terminal tail of Hxt11 confers membrane stability to the Hxt2 sugar transporter and improves xylose fermentation in the presence of acetic acid

Abstract: Hxt2 is a glucose repressed, high affinity glucose transporter of the yeast Saccharomyces cerevisiae and is subjected to high glucose induced degradation. Hxt11 is a sugar transporter that is stably expressed at the membrane irrespective the sugar concentration. To transfer this property to Hxt2, the N‐terminal tail of Hxt2 was replaced by the corresponding region of Hxt11 yielding a chimeric Hxt11/2 transporter. This resulted in the stable expression of Hxt2 at the membrane and improved the growth on 8% d‐glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…It should be noted that in this study, the K m values for Hxt2 (C505P) and both fusions were obtained using a lower cell density (OD 600 of 10 instead of 100) and longer uptake times (10 instead of 1 min) compared with our previous study (Shin et al . ). This modification resulted in more reliable uptake data.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It should be noted that in this study, the K m values for Hxt2 (C505P) and both fusions were obtained using a lower cell density (OD 600 of 10 instead of 100) and longer uptake times (10 instead of 1 min) compared with our previous study (Shin et al . ). This modification resulted in more reliable uptake data.…”
Section: Discussionmentioning
confidence: 97%
“…The subfamily of expressed Hxt genes can be readily used in the gene shuffling approach as they exhibit a high homology on DNA level, which ranges from 64% to 99% (Boles and Hollenberg 1997;Reifenberger et al 1997). Furthermore, previous studies on engineered Hxt chimeras have already indicated that they maintain their activity and that by this approach the affinity for D-glucose can be modulated (Kasahara and Kasahara 2003;Kasahara et al 2004Kasahara et al , 2007Kasahara et al , 2009Shin et al 2017). Kasahara and coworkers identified the key amino acids responsible for the affinity towards D-glucose; although mutations that had a negative effect on the affinity for D-glucose were found (Kasahara et al 2006(Kasahara et al , 2009(Kasahara et al , 2011Kasahara and Kasahara 2010), the impact of the mutations on the D-xylose affinity was not investigated.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the various Hxt transporters, the Hxt11 N366T mutant is equipped with the most favorable Dxylose uptake characteristics, i.e., a K m of 46 mM and a V max of 76 nmol/mgDW.min (Table 1) (Shin et al, 2015). Another advantage of Hxt11 is that this normally cryptic transporter is stably expressed at high D-glucose concentrations at the plasma membrane without any sign of degradation (Shin et al, 2015(Shin et al, , 2017 in contrast to for instance Hxt2 (Kruckeberg et al, 1999;Shin et al, 2017) and Hxt7 (Krampe et al, 1998;Snowdon and van der Merwe, 2012). The structure of Hxt36 (Nijland et al, 2014) (Figure 2) and Gal2 (Farwick et al, 2014) were modeled according to the crystal structure of XylE, a MFS transporter of Escherichia coli with D-xylose in the binding site (Sun et al, 2012).…”
Section: D-xylose Transportmentioning
confidence: 99%
“…For instance, sugar utilization for biofuel production was improved by engineering xylose/ glucose importers (Hamacher et al, 2002;N. Li et al, 2016;Nijland et al, 2016;Shin et al, 2017). Likewise, the yields of many biofuel molecules (butanol, isopentanol and limonene, etc.)…”
Section: Introductionmentioning
confidence: 99%